4-Coumarate-CoA Ligase-Like Gene OsAAE3 Negatively Mediates the Rice Blast Resistance, Floret Development and Lignin Biosynthesis - Liu, Hao; Guo, Zhenhua; Gu, Fengwei; Ke, Shanwen; Sun, Dayuan; Dong, Shuangyu; Liu, Wei; Huang, Ming; Xiao, Wuming; Yang, Guili; Liu, Yongzhu; Guo, Tao; et al. (Frontiers in Plant Science, 2017)
Although adenosine monophosphate (AMP) binding domain is widely distributed in multiple plant species, detailed molecular functions of AMP binding proteins (AMPBPs) in plant development and plant-pathogen interaction remain unclear. In the present study, we identified an AMPBP OsAAE3 from a previous analysis of early responsive genes in rice during Magnaporthe oryzae infection. OsAAE3 is a homologue of Arabidopsis AAE3 in rice, which encodes a 4-coumarate-Co-A ligase (4CL) like protein. A phylogenetic analysis showed that OsAAE3 was most likely 4CL-like 10 in an independent group. OsAAE3 was localized to cytoplasm, and it could be expressed in various tissues. Histochemical staining of transgenic plants carrying OsAAE3 promoter-driven GUS (β-glucuronidase) reporter gene suggested that OsAAE3 was expressed in all tissues of rice. Furthermore, OsAAE3-OX plants showed increased susceptibility to M. Oryzae, and this finding was attributable to decreased expression of pathogen-related 1a (PR1) and low level of peroxidase (POD) activity. Moreover, OsAAE3 over-expression resulted in increased content of H2O2, leading to programmed cell-death induced by reactive oxygen species (ROS). In addition, OsAAE3 over-expression repressed the floret development, exhibiting dramatically twisted glume and decreased fertility rate of anther. Meanwhile, the expressions of lignin biosynthesis genes were significantly decreased in OsAAE3-OX plants, thereby leading to reduced lignin content. Taken together, OsAAE3 functioned as a negative regulator in rice blast resistance, floret development and lignin biosynthesis. Our findings further expanded the knowledge in functions of AMBPs in plant floret development and the regulation of rice-fungus interaction.